Hubungan Peran Orang Tua Dengan Perilaku Merokok Pada Remaja Di Wilayah Kerja Puskesmas Galang - Badri, Isna Aglusi; Hayat, Nahrul; Rahmadeni, Asfri Sri (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Adolescence is a period of growth and development of a person in achieving physical, mental, social, and emotional maturity. This period of self-discovery is not uncommon for teenagers to spend a lot of time outside with friends. This stage causes a lot of negative behavior that will appear, one of which is the behavior of adolescents in smoking. The incidence of smoking in adolescents aged 10 years and over every year continues to increase. The purpose of this study was to see the relationship between the role of parents and smoking behavior in adolescents in the work area of the Galang Health Center, Nguan Island, Batam. The research design is an analytical survey with a cross-sectional approach. The sampling technique used is total sampling. The results obtained 51.4% the role of parents is not good. Smoking behavior of adolescents 88.6% of adolescents smoke. A small proportion (14.3%) are teenage girls who also smoke. The results of the Chi-square test p = 0.029, there is a relationship between the role of parents and adolescent smoking behavior. It is recommended for parents to always pay more attention to children, especially when they are teenagers, provide a good example in the family environment and always provide education to teenagers, especially smoking is not only damaging to themselves but also to many people.